Hubungan Penggunaan Media Sosial Facebook dengan Perilaku Sosial Siswa Kelas Tinggi SD Negeri 57 Oro Gading Kabupaten Bulukumba - Satriani DH; Abd. Hafid; Rahmayani Rahmayani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study is a quantitative study with a correlation model that aims to determine the relationship between the use of facebook social media and the social behavior of high-class students at SD Negeri 57 Oro Gading, Kindang District, Bulukumba Regency with a population of 46 students. Data collection is done by using a questionnaire. The data analysis technique used descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistics, the results of research on the use of social media Facebook have an average of 93.93 with a percentage of 56% in the medium category and students' social behavior has an average of 89.83 with a percentage of 56% in the medium category. Based on the results of inferential statistics, the rtable at a significance level of 5% is 0.290 so that rcount ≥  rtable (0.363 ≥ 0.290). Thus H1 accepted and H0 rejected. So that the results of the study can be concluded that there is a significant relationship between the use of Facebook social media and the social behavior of high-class students at SD Negeri 57 Oro Gading, Kindang District, Bulukumba Regency.